1980
DOI: 10.1002/1097-0142(19800415)45:8<2198::aid-cncr2820450832>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate of 147 mammary carcinomas

Abstract: In 147 cases of mammary carcinoma, 388 serial mammographies were performed before final treatment. The average retrospective observation time was 27 months with a range of two months to 11 years. The number of serial mammographies per case ranged between two and 11. The tumor volume doubling times (TV); obtained by measuring the growth of the tumor nucleus shadow in the mammographies, ranged from 44 to 1869 days with an average of 212 days. No correlation between volume doubling time and histologic differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
77
1
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 11 publications
(1 reference statement)
10
77
1
2
Order By: Relevance
“…The estimated average tD of 282 days in this study was in the range of other reported studies (105-327 days) (1)(2)(3)(6)(7)(8)(9)(10)(11)(12) . Previous reporting of tumour growth and histopathological findings are inconsistent and some of these studies use outdated histopathological measures making a direct comparison difficult.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The estimated average tD of 282 days in this study was in the range of other reported studies (105-327 days) (1)(2)(3)(6)(7)(8)(9)(10)(11)(12) . Previous reporting of tumour growth and histopathological findings are inconsistent and some of these studies use outdated histopathological measures making a direct comparison difficult.…”
Section: Discussionsupporting
confidence: 76%
“…Previous reporting of tumour growth and histopathological findings are inconsistent and some of these studies use outdated histopathological measures making a direct comparison difficult. Nevertheless, patient age (8,9,11) , axillary lymph node involvement (2,7) and advanced TNM stage (11,12) have been shown to correlate with tD. Kusama et al and Kuroshi et al both found that tumour volume doubling time correlated with survival (9,11) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations